Grace Williams: capstone - Williams, Grace, artist (Colorado State University. Libraries, 2023)
The artist's statement: As a graphic designer Grace Williams tries to promote change and awareness in her work. Her work is made to stimulate a change in the way people think. To either bring awareness about a specific issue or bring people together to create change in our world. Grace believes that she can use her work in a positive way to help better the world. The mediums used to create Grace's work are mostly digital. She uses a verity of adobe programs, along with an app called procreate. However, there is also a wide verity of mixed mediums, media, and materials used to create her work. In her work she has used many different analogue drawing mediums, fabrics, many different papers, and surfaces. There is no limit to what a project could need. The process of making her work is thorough and efficient. She first starts with an inquiry about the project. She uses this first step to gather information, requirements, and restrictions about the project. This goes for both personal projects and client-based projects. After the guides are set, she can begin her research and start sketching out the preliminary ideas. Then a first render of the project is made. This first render is the first look at what the project could become. There are usually a few options to choose from as well. Grace then runs a Q & A with the client or other colleagues to ask what is working, what's not, and what design is the most successful. This process of creation and following check points are the meat of what makes her work successful. After these initial first steps the project is fulling underway. The process in short repeats these steps as many times as need throughout the different paths of the project. Every project is different and will require a different way of working each time. This procedure was designed to be flexible and can repeat or shuffle to the needs of the individual project. Grace has worked on many different types and styles of projects in her studies. She has designed a layout for a magazine, illustrated a children's book, designed a brand from scratch, and much more. However, throughout her work there are similar inspirations and themes. These inspirations come from nature, history, and current issues. Nature has a chaotic systematic order for life that she can use as blueprint to create. History holds lessons that she can learn from and use in her work. While the current issues of the world provide her with a compass in which to guide her morals and subject matter. This inspiration comes from her own life experiences and what she holds most important to her. Each of these topics builds the backbone of why Grace became an artist. Grace's work is a representation of the world as she sees it and how she sees it could be. She sees her work as an avenue for people to come together. This avenue then being a stimulus for change. She wants to show the world through her work how life could be and how life is. Through her work she wants to represent a better world for everyone. She wants her work to give voice to those that have none, rally the people together, and show people the reality of our world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design